CARTOGRAPHY OF THE PIONEER FRONTS AND CONTRIBUTION TO THE ANALYSIS OF DEFORESTATION IN PARÁ - Thalês, Marcelo; Poccard-Chapuis, René; Ruivo, Maria de Lourdes Pinheiro (Mercator; Vol 20 (2021)DO - 10.4215/rm2021.e20018, 2021)
The present study is based on a diachronic cartography of the pioneer fronts in the Brazilian state of Pará, which was used to analyze deforestation patterns between 2002 and 2017. For this cartography, the territory of Pará was divided into cells of 5 km x 5 km, in which the cumulative percentage of deforestation was calculated for each year from 2002 to 2017, with the data being classified in five evolutionary phases of the pioneer front. This cartography permitted the systematic representation of the spatiotemporal dynamics of deforestation in the study area and the evaluation of regional patterns, which allowed the pioneer regions to be delimited and characterized in three principal categories – expansion, stabilization, and consolidation. By relating the pioneer fronts to deforestation rates in each period, it was possible to classify them as consolidated territories, focused on the intensification of agricultural practices, or under expansion, through a strategy of occupation, in addition to areas free of deforestation. The approach adopted in the present study is easy to understand and can provide important guidelines for decision-makers in different administrative spheres, contributing to the formulation of effective measures for the control of deforestation and the sustainable development of the region. Keywords : Pioneer fronts. Deforestation. Territorial Dynamics. Brazilian Amazon.